2015
DOI: 10.1051/0004-6361/201322035
|View full text |Cite
|
Sign up to set email alerts
|

Supernova spectra below strong circumstellar interaction

Abstract: We construct spectra of supernovae (SNe) interacting strongly with a circumstellar medium (CSM) by adding SN templates, a blackbody continuum, and an emission-line spectrum. In a Monte Carlo simulation we vary a large number of parameters, such as the SN type, brightness and phase, the strength of the CSM interaction, the extinction, and the signal to noise ratio (S/N) of the observed spectrum. We generate more than 800 spectra, distribute them to ten different human classifiers, and study how the different si… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
55
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 103 publications
(178 reference statements)
6
55
1
Order By: Relevance
“…These SNe Ia-CSM have been proposed to happen when white dwarfs explode inside the CSM of its nondegenerate binary companion (see Silverman et al 2013, and references therein). In simulations by Leloudas et al (2015) it was shown that SNe Ia-CSM can be mistaken for genuine SNe IIn under some circumstances. Leloudas et al (2015) shows that a SN Ia (of typical peak magnitude M ≈ −19) can be hidden under an apparent SN IIn spectrum if the CSI is strong and the peak magnitude of the SN IIn is M ≈ −20.9.…”
Section: Possible Contaminants In the Sample?mentioning
confidence: 99%
“…These SNe Ia-CSM have been proposed to happen when white dwarfs explode inside the CSM of its nondegenerate binary companion (see Silverman et al 2013, and references therein). In simulations by Leloudas et al (2015) it was shown that SNe Ia-CSM can be mistaken for genuine SNe IIn under some circumstances. Leloudas et al (2015) shows that a SN Ia (of typical peak magnitude M ≈ −19) can be hidden under an apparent SN IIn spectrum if the CSI is strong and the peak magnitude of the SN IIn is M ≈ −20.9.…”
Section: Possible Contaminants In the Sample?mentioning
confidence: 99%
“…SLSNII are H rich. Leloudas et al (2015) refer to Extreme Emission Line Galaxies (EELG) observations. For spectroscopy they used FORS2 and X shooter on the VLT, OSIRIS on the GTC and IMACS on Magellan.…”
Section: Leloudas Et Al (2015) Sn Galaxy Host Surveymentioning
confidence: 99%
“…Narrow lines originate from the host galaxy, downstream of the shock produced by collision of the fast moving ejecta with the CSM (see Leloudas et al 2015 and references therein). We report in Table 2 the data presented by Leloudas et al (2015) in their table B1. For each galaxy the observed line ratios are followed in the two next rows by the best fitting results calculated by shock dominated (SD) models (ml1-ml26) and radiation dominated (RD) models (mll1-mll26) which account for the photoionization flux from the SB + shocks, respectively.…”
Section: Leloudas Et Al (2015) Sn Galaxy Host Surveymentioning
confidence: 99%
“…These events are interpreted as thermonuclear SNe interacting with H-rich CSM (Hamuy et al 2003;Aldering et al 2006;Dilday et al 2012;Taddia et al 2012;Silverman et al 2013;Fox et al 2015), although a CC origin has also been proposed (Benetti et al 2006;Inserra et al 2014). Their spectra are well represented by the sum of narrow Balmer emission lines and SN Ia spectra diluted by a blue continuum (Leloudas et al 2015b).…”
Section: Introductionmentioning
confidence: 99%